The Influence of Ghanaian Headteachers’ Creative Problem-Solving Attributes on Teachers’ Person-Environment Fit Dimensions and Retention Relationship - Semarco, Stanley K.M. Cho, Seokhee (African Journal of Education and Practice, 2017)
Purpose: The study examined three person-environment fit dimensions and retention within the framework of Cho’s (2003) dynamic creative problem-solving ability attributes. The purpose was to establish the effect of head teachers’ knowledge and skills, divergent thinking, convergent thinking, motivation, and environment on the linkage between teachers’ person-environment fit dimensions and their retention intentions. Methodology: Questionnaires from 279 head teachers were on their creative problem-solving ability attributes. Questionnaires from 558 teachers were on their perceived person-environment fit dimensions and retention intentions. The quantitative oriented correlational cross-sectional research survey design was employed. The correlation test and structural equation modelling techniques were employed to analyze the relationships among the creative problem solving ability attributes, perceived person-environment fit dimensions and retention intentions. Findings: With the exception of the motivation – knowledge path which was insignificant, findings from the analysis showed that knowledge and skills attribute significantly mediate the relationship between the dynamic creative problem solving ability attributes and the personbrand fitting ability of head teachers. The person-brand fit indirectly predicts teacher retention intention, with the person-job fit and person-organisation fit being significant mediators. Theory, practice and policy: Theoretically, the study’s Dynamic System Model of Creative Fit for Retention casts creative problem-solving ability attributes within the framework of personenvironment fit and employee retention. The study’s findings that leaders need to continue to creatively fit their followers to the work environment to enhance retention intentions; the associated policy implications and future research directions are discussed.
Research Article
Keywords: Creative Problem-Solving, Person-Environment Fit, Retention